Analisis Pelaksanaan Asesmen Formatif dan Sumatif pada Mata Pelajaran Pendidikan Agama Islam Kelas 4 di SDN 2 Konda - Ita Nurwati; Nurlathifah Thulfitrah B (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to systematically analyze the implementation of formative and summative assessments in Grade IV Islamic Religious Education (PAI) at SDN 2 Konda within the framework of the Merdeka Curriculum. The research employs a qualitative approach with a case study design to obtain an in-depth and contextual understanding of classroom assessment practices. Data were collected through classroom observations, in-depth interviews with teachers, the principal, and parents, as well as an analysis of curriculum documents and various assessment instruments used throughout the learning process. The data were analyzed using thematic coding techniques supported by NVivo software, guided by the Formative Summative Continuum framework to examine the alignment and integration between both assessment types. The findings indicate that teachers have regularly implemented formative assessment through digital quizzes, direct observation, reflective discussions, and continuous feedback, which have increased student participation and strengthened competency mastery. Meanwhile, summative assessment was conducted at the end of the semester through written tests and project-based assignments; however, it still primarily emphasizes cognitive aspects and has not fully integrated formative assessment evidence. The study also identifies limitations in the use of multidimensional rubrics, continuous portfolio management, and meaningful parental involvement in the overall evaluation process.